Kesulitan Belajar Akademik dalam Proses Pembelajaran - Habsy, Bakhrudin All; Soviana, Amelia Fauziyyah; Putri, Abrillianty Tivany Surya; Hati, Adinda Mutiara (TSAQOFAH, 2024)
Learning difficulties are an important problem in the world of education that requires deep understanding. This article aims to provide a comprehensive overview of understanding and identifying learning difficulties. Learning difficulties refer to the difficulties a person experiences in understanding and processing information taught in a formal educational environment. This article presents various aspects related to this phenomenon, including its causative factors, identifying marks, and their impact on the development of each individual. The causes of learning difficulties include internal factors and external factors. Some signs that can be used to identify learning difficulties include difficulty reading, writing, arithmetic. It is important for educators, parents, and health professionals to recognize these signs early so that appropriate interventions can be provided. This article also discusses the impact of learning difficulties, namely inhibition of children's growth and development, disruption of children's interaction and environment. In addition, various identification and intervention strategies that can help those with learning difficulties are presented, such as psychological assessments, special education support, and adaptive learning approaches. This article provides a solid foundation to encourage greater understanding and interest in these educational issues.